Evaluation of Ethnicity Effect on Intranasal Esketamine Pharmacokinetics by Population Pharmacokinetic Modeling Using Data From a Japanese Phase 2b Study. Issue 4 (22nd December 2022) - Kurosawa, Ken; Shibuya, Minaka; Shimizu, Hiroko; Pérez‐Ruixo, Carlos
Abstract: Esketamine is used for the treatment of treatment‐resistant depression in many countries. A population pharmacokinetic (popPK) model of esketamine and its metabolite (noresketamine) has been previously developed, which included Asian race and Japanese ethnicity as covariates on their exposures. The present study aimed to update the popPK model by adding new data from a phase 2b study in Japanese patients and reassess intrinsic and extrinsic factors on esketamine and noresketamine exposures. The updated model identified the effects of body weight on the fraction of the esketamine dose absorbed in the nasal cavity and elimination rate constant of esketamine, and Asian race on the apparent clearance of noresketamine. The model predicted that an increase of 30 kg of body weight would decrease esketamine exposures by ≈20%. Noresketamine exposures would be affected by Asian race and body weight. However, those newly identified covariates were not considered to have clinically relevant impacts, and therefore dose adjustments were not necessary. In conclusion, the popPK model of esketamine and noresketamine was successfully updated and suggested that interindividual variability of esketamine exposures can be better explained by body weight, rather than by race/ethnicity. The new findings obtained in this study should be useful information for the further development of esketamine and for clinical practice in the future.